Sleep. 1: Obstructive sleep apnoea/hypopnoea syndrome: definitions, epidemiology, and natural history. - Stradling, JR; Davies, R (2004)
Arguments over the definition of obstructive sleep apnoea/hypopnoea syndrome (OSAHS) have still not been satisfactorily resolved. As a result, robust estimates of the prevalence of OSAHS are not possible. New approaches are needed to identify those who have "CPAP responsive" disease, enabling more accurate estimates to be made of the prevalence of the sleep apnoea syndrome in the community.